Advances in Applied Mathematics and Global Optimization In Honor of Gilbert Strang - Gao, David Y.; Sherali, Hanif D. (Advances in Mechanics and Mathematics, 2009)
The articles that comprise this distinguished annual volume for the Advances in Mechanics and Mathematics series have been written in honor of Gilbert Strang, a world renowned mathematician and exceptional person. Written by leading experts in complementarity, duality, global optimization, and quantum computations, this collection reveals the beauty of these mathematical disciplines and investigates recent developments in global optimization, nonconvex and nonsmooth analysis, nonlinear programming, theoretical and engineering mechanics, large scale computation, quantum algorithms and computation, and information theory. Much of the material, including the various methodologies, is written for nonexperts and is intended to stimulate graduate students and young faculty to venture into this rich domain of research; it will also benefit researchers and practitioners in several areas of applied mathematics, mechanics, and engineering.